A comprehensive study of single-flawed granite hydraulically fracturing with laboratory experiments and flat-jointed bonded particle modeling. (December 2021) - Zhang, Rui; Zhao, Cheng; Yang, Chengye; Xing, Jinquan; Morita, Chihiro
Abstract: Understanding the mechanisms of crack initiation and development is important for utilizing the hydraulic fracturing in practical engineering applications. In this study, hydraulic fracturing experiments were conducted on granite specimens containing a single pre-existing flaw, and the failure processes were analyzed using the digital image correlation method. A flat-jointed bonded particle model was built with a modified fluid flow algorithm to better understand the fracture behavior under the experimental conditions. Combining the DIC strain fields and the simulated displacement fields, we found that shear behavior with a small value also emerges ahead of the tips of the microcracks and was covered by the subsequent tensile behavior, as a result, shear strain could not be observed in the experiments. A comparison between the strain localization and the microcracks revealed that the fracturing process observed in the experiments had two stages: the isolated strain localization formed during Stage I, mainly resulting from the increase in microcracks, and the continuous high tensile strain path formed during Stage II. Additionally, the effect of the different flaw inclination angles was discussed from two perspectives: the different types of macrocracks and the change in the fracturing liquid pressure.